Neonatal acute apendicitis, case report - Romero Rojas, Nery (2016)
Introduction. Acute appendicitis is a rare disease in newborns with a high mortality because of unspecific clinical features. We report a case of non-perforated acute appendicitis in a newborn at the San Bartolome Hospital in Lima. Case report. A female newborn weighing 3 170 g in the first day repelled maternal lactation; at the third day, she presented 39°C fever, and later, abdominal distention, constipation, and abundant vomiting. The X-ray films showed a distended gastric camera and paralytic ileum; other auxiliary exams were inconclusive. She was operated with the diagnosis of intestinal obstruction; we found the ceccal appendix with multiple lax adhesions to the ileum. The pathologic study showed an acute not perforated gangrenous appendicitis. Appendicitis must be considered in the differential diagnosis of a neonatal surgical emergency.